Early Postnatal Hypotension and Developmental Delay at 24 Months of Age among Extremely Low Gestational Age Newborns - Logan, J. Wells (Arch Dis Child Fetal Neonatal Ed, 2010)
OBJECTIVES: To evaluate, in extremely low gestational age newborns (ELGANs), relationships between indicators of hypotension during the first 24 postnatal hours and developmental delay at 24 months of age. METHODS: The 945 infants in this prospective study were born at < 28 weeks, were assessed for 3 indicators of hypotension in the first 24 postnatal hours, and were evaluated with the Bayley Mental Development Index (MDI) and Psychomotor Development Index (PDI) at 24 months corrected age. Indicators of hypotension included: 1) mean arterial pressure (MAP) in the lowest quartile for gestational age; 2) treatment with a vasopressor; and 3) blood pressure lability, defined as the upper quartile for the difference between the lowest and highest MAP. Logistic regression was used to evaluate relationships between hypotension and developmental outcomes, adjusting for potential confounders. RESULTS: 26% of the cohort had an MDI < 70 and 32% had a PDI < 70. Low MDI and PDI were significantly associated with low gestational age, which in turn, was associated with receipt of vasopressor treatment. Blood pressure in the lowest quartile for gestational age was associated with vasopressor treatment and labile blood pressure. After adjusting for potential confounders, none of the indicators of hypotension was associated with MDI < 70 or PDI < 70. CONCLUSIONS: In this large cohort of ELGANs, we found little evidence that early postnatal hypotension is associated with developmental delay at 24 months corrected gestational age.